2011
DOI: 10.1136/bmj.d7434
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of implantable hip devices with different bearing surfaces: systematic appraisal of evidence

Abstract: Objective To determine comparative safety and effectiveness of combinations of bearing surfaces of hip implants.Design Systematic review of clinical trials, observational studies, and registries.Data sources Medline, Embase, Cochrane Controlled Trials Register, reference lists of articles, annual reports of major registries, summaries of safety and effectiveness for pre-market application and mandated post-market studies at the United States Food and Drug Administration.Study selection Criteria for inclusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…In a simulation, polyethylene wear when combined with a ceramic head is half that of polyethylene combined with metal [1]. Clinical studies have also yielded very good long-term outcomes for this articulating couple [2,3]. These findings show that an articulating couple with optimal wear properties is of crucial importance in revision hip surgery, especially in younger patients.…”
Section: Introductionmentioning
confidence: 66%
“…In a simulation, polyethylene wear when combined with a ceramic head is half that of polyethylene combined with metal [1]. Clinical studies have also yielded very good long-term outcomes for this articulating couple [2,3]. These findings show that an articulating couple with optimal wear properties is of crucial importance in revision hip surgery, especially in younger patients.…”
Section: Introductionmentioning
confidence: 66%
“…Studies have shown that there is no difference in functional outcomes, measured by the Harris Hip Score, between different types of hip implants 2 years after the total hip arthroplasty, although metal-on-polyethylene implants had slightly better functional scores within the fi rst 2 years after THA. 19 Conclusive evidence has not been reached for a general recommendation on material type. Here, we will discuss general characteristics of each type of implant material and the advantages and disadvantages associated with them.…”
Section: Implant Materialsmentioning
confidence: 96%
“…The most common causes of implant failure are infection, dislocation, wear, instability, loosening, or other mechanical failure. 19 Differences in these implants are the materials used, sizing of the implant components, and fi xation of the implant. Each option has its own advantages and disadvantages that can infl uence the long-term function of the artifi cial hip and affect the risk of postprocedure complications.…”
Section: Implant Optionsmentioning
confidence: 99%
“…The thermal oxidation behavior of Al ion implanted Ti nitride films has been studied in dry oxygen atmosphere and found that Al implantation caused the oxidation rate of TiN films to slow down at the initial stage of oxidation [222]. Until recently, there is limited evidence regarding comparative effectiveness of various hip implant bearings, especially metal on metal or ceramic on ceramic implants compared with traditional metal on polyethylene or ceramic on polyethylene bearings [223].…”
Section: Aluminium (Or Aluminum) and Ceramicsmentioning
confidence: 99%